Mismatched dNTP incorporation by DNA polymerase β does not proceed via globally different conformational pathways(†) - Tang, Kuo-Hsiang (Oxford University Press, 2008)
Understanding how DNA polymerases control fidelity requires elucidation of the mechanisms of matched and mismatched dNTP incorporations. Little is known about the latter because mismatched complexes do not crystallize readily. In this report, we employed small-angle X-ray scattering (SAXS) and structural modeling to probe the conformations of different intermediate states of mammalian DNA polymerase β (Pol β) in its wild-type and an error-prone variant, I260Q. Our structural results indicate that the mismatched ternary complex lies in-between the open and the closed forms, but more closely resembles the open form for WT and the closed form for I260Q. On the basis of molecular modeling, this over-stabilization of mismatched ternary complex of I260Q is likely caused by formation of a hydrogen bonding network between the side chains of Gln(260), Tyr(296), Glu(295) and Arg(258), freeing up Asp(192) to coordinate MgdNTP. These results argue against recent reports suggesting that mismatched dNTP incorporations follow a conformational path distinctly different from that of matched dNTP incorporation, or that its conformational closing is a major contributor to fidelity.